Disk Turbulence and Star Formation Regulation in High-z Main-sequence Analog Galaxies - Laura Lenkić; Deanne B. Fisher; Alberto D. Bolatto; Peter J. Teuben; Rebecca C. Levy; Jiayi Sun; Rodrigo Herrera-Camus; Karl Glazebrook; Danail Obreschkow; Roberto Abraham (The Astrophysical Journal)
The gas-phase velocity dispersions in disk galaxies, which trace turbulence in the interstellar medium, are observed to increase with lookback time. However, the mechanisms that set this rise in turbulence are observationally poorly constrained. To address this, we combine kiloparsec-scale Atacama Large Millimeter/submillimeter Array observations of CO(3−2) and CO(4−3) with Hubble Space Telescope observations of H α to characterize the molecular gas and star formation properties of seven local analogs of main-sequence galaxies at z ∼ 1–2, drawn from the DYNAMO sample. Investigating the “molecular gas main sequence” on kiloparsec scales, we find that galaxies in our sample are more gas-rich than local star-forming galaxies at all disk positions. We measure beam-smearing-corrected molecular gas velocity dispersions and relate them to the molecular gas and star formation rate surface densities. Despite being relatively nearby ( z ∼ 0.1), DYNAMO galaxies exhibit high velocity dispersions and gas and star formation rate surface densities throughout their disks, when compared to local star-forming samples. Comparing these measurements to predictions from star formation theory, we find very good agreements with the latest feedback-regulated star formation models. However, we find that theories that combine dissipation of gravitational energy from radial gas transport with feedback overestimate the observed molecular gas velocity dispersions.